Using Adele’s “Someone Like You” to Teach Verbs Tenses and Passive Forms - Ariya Jati (Master Program in Linguistics, Diponegoro University, 2013)
This paper is about how to use Adele’s “Someone Like You” to teach tenses and passive forms. Adele’s song lyric was potentially used in an English-as-a Foreign Language (EFL) classroom. This study is to provide a practical alternative to the teaching of tenses and passive forms. The teaching is performed in three phases namely text completion, verb categorization, and sentence construction. The teaching is expected the students to demonstrate their receptive and productive skills in English language by using the lyric. (By such a teaching, the students are expected to be able to demonstrate their receptive and productive skills in English language by using the lyric.)Makalah ini tentang penggunaan lirik “Someone Like You” karya Adele untuk mengajarkan kala dan bentuk pasif. Lirik lagu Adele tersebut dapat digunakan di dalam kelas dengan bahasa Inggris sebagai bahasa asing. Kajian ini untuk memberikan alternatif praktis bagi pengajaran kala dan bentuk pasif bagi mahasiswa EFL. Pengajaran dilakukan dalam tiga tahap, yaitu: pengisian teks, kategorisasi kata kerja, dan penyusunan kalimat. Pengajaran ini diharapkan dapat memungkinkan mahasiswa menampilkan keterampilan reseptif dan produktif mereka dalam berbahasa Inggris melalui lirik tersebut.